TEKNIK PENGKONDISIAN AVERSI DALAM MENGATASI PERILAKU MEMBOLOS - Rukayah, Nur Rukayah (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
This study aims to determine the effectiveness of the application of aversion conditioning to reduce truancy habits in students of MTsN 8 Ngawi. This research includes qualitative research with phenomenonolgy studies. The research target was the ninth grade students of MTsN 8 Ngawi. The data collection methods used by researchers are interviews, observation, and documentation. Where the data that has been collected afterwards is organized and classified so that it can answer the formulation of the problem. The results of research conducted by researchers at MTsN 8 Ngawi Skipping school is no longer a rare thing. Almost all schools and levels of education must have the phenomenon of skipping school, so that school learning is not effective. Based on research conducted by researchers at MTsN 8 Ngawi, researchers concluded that: There are several reasons why students want to skip class, among which the most common are bored / lazy, dislike for the teacher who teaches or the lesson that is taking place and the influence of peers who invite out of class together. The aversion method that researchers choose to reduce the habit of skipping class during class hours at MTsN 8 Ngawi students in class IX is quite effective, because it can be seen from the decrease in the habit of students skipping class IX. And the factors that hinder the aversion conditioning process in class IX MTsN 8 Ngawi include: insufficient bk lesson hours, lack of concern for the students, and the lack of awareness of the students' behavior. Keywords: truancy behavior, aversion technique